Hypoxia-induced preadipocyte factor 1 expression in human lung fibroblasts through ERK/PEA3/c-Jun pathway - Wun-Hao Cheng; Chia-Ling Chen; Jing-Yun Chen; Chien-Huang Lin; Bing-Chang Chen (BMC, 2021)
Abstract Background Several studies have reported that hypoxia plays a pathological role in severe asthma and tissue fibrosis. Our previous study showed that hypoxia induces A disintegrin and metalloproteinase 17 (ADAM17) expression in human lung fibroblasts. Moreover, preadipocyte factor 1 (Pref-1) is cleaved by ADAM17, which participates in adipocyte differentiation. Furthermore, Pref1 overexpression is involved in tissue fibrosis including liver and heart. Extracellular signal-regulated kinase (ERK) could active downstram gene expression through polyoma enhancer activator 3 (PEA3) phosphorylation. Studies have demonstrated that PEA3 and activator protein 1 (AP-1) play crucial roles in lung fibrosis, and the Pref-1 promoter region contains PEA3 and AP-1 binding sites as predicted. However, the roles of ERK, PEA3, and AP-1 in hypoxia-stimulated Pref-1 expression in human lung fibroblasts remain unknown. Methods The protein expression in ovalbumin (OVA)-induced asthmatic mice was performed by immunohistochemistry and immunofluorescence. The protein expression or the mRNA level in human lung fibroblasts (WI-38) was detected by western blot or quantitative PCR. Small interfering (si) RNA was used to knockdown gene expression. The collaboration with PEA3 and c-Jun were determined by coimmunoprecipitation. Translocation of PEA3 from the cytosol to the nucleus was observed by immunocytochemistry. The binding ability of PEA3 and AP-1 to Pref-1 promoter was assessed by chromatin immunoprecipitation. Results Pref-1 and hypoxia-inducible factor 1α (HIF-1α) were expressed in the lung sections of OVA-treated mice. Colocalization of PEA3 and Fibronectin was detected in lung sections from OVA-treated mice. Futhermore, Hypoxia induced Pref1 protein upregulation and mRNA expression in human lung fibroblasts (WI38 cells). In 60 confluent WI-38 cells, hypoxia up-regulated HIF-1α and Pref-1 protein expression. Moreover, PEA3 small interfering (si) RNA decreased the expression of hypoxia-induced Pref1 in WI38 cells. Hypoxia induced PEA3 phosphorylation, translocation of PEA3 from the cytosol to the nucleus, PEA3 recruitment and AP-1 binding to the Pref1 promoter region, and PEA3-luciferase activity. Additionally, hypoxia induced c-Jun-PEA3 complex formation. U0126 (an ERK inhibitor), curcumin (an AP1 inhibitor) or c-Jun siRNA downregulated hypoxia-induced Pref-1 expression. Conclusions These results implied that ERK, PEA3, and AP1 participate in hypoxiainduced Pref1 expression in human lung fibroblasts.